Gender Differences in the Manifestation of Aggressive Behavior in Adolescents - Baktygali А.; Akhtaeva, N.S.; Sadykova, N.M. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2019)
This article presents the results of a study of thegender difference in presence of aggressive behavior of the teenagers. The gender difference in presence of aggressive behavior was determined and analyzed by the following methods as: Bassa-Darky questionnaire, The method of “Personal aggress and conflict” ( Ilyn E. P. and Kovalev P. A.) proposed for determination of subject to the conflict and aggress in purpose of personal characteristic. Scale: short temper, touchiness, intransigence, compromise, vindictiveness, intolerance to the others opinions, suspicion; positive aggressiveness, negative aggressiveness, conflict. The method of diagnosis of the self-esteem mental states (by Aizenk) proposed for determination of the level of following important mental traits: anxiety, frustration, aggressiveness and rigidity. For math treatment of the data, there was used the Spearmen’s correlation coefficient and U-criteria Manna-Whitney in the program of statistical treatment SPSS16. By the results of empirical study of gender differences in presence of aggressive behavior of teenagers, there are was confirmed the hypothesis, that the boys more often show aggressive behavior in comparison with girls, but girls dominated by physical and verbal types of aggressive behavior. By results of statistical analyses by Manna-Whitney criteria, there are was determined, that rigidity, immutability of behavior more pronounced at the boys. Boys often use physical force against other persons, and also express their negative feelings both through the form (cry, squeal), and through the content of verbal responses (curses, threats). In general, boys are more likely to show aggressive behavior, unlike girls.